Finite element assessment of a disc-replacement implant for treating scoliotic deformity. (April 2021) - Taleghani, Eric; Singh, Alexander; Hachem, Bahe; Benoit, David; Rustagi, Rohit; Vithoulkas, George; Mac-Thiong, Jean-Marc; Syed, Hasan
Abstract: Background: Bracing and spinal fusion surgery have long been the primary methods for idiopathic scoliosis correction; however, there exist multiple limitations with both techniques. Growth modulation techniques have recently been attempted, but are typically performed across multiple vertebral elements. The aim of this study was to quantify the corrective abilities of a dual-angled, wedge shaped, rigid disc implant designed to correct spinal deformity. Methods: The 3D spinal geometry of four patients was reconstructed using calibrated radiographs, from which personal finite element models were created. Coronal and sagittal Cobb angles and axial stress distribution were calculated pre- and post- simulation of device implantation at the apical vertebral element. Findings: Insertion of a rigid wedged implant resulted in up to 90.1% coronal correction with kyphotic normalization, and reduced axial stress differential within adjacent vertebrae by up to 83.3%. This correction in axial stress differential was seen to propagate to subjacent vertebrae in both rostral and caudal directions. Insertion of two implants yielded greater correction with respect to all three measures. Interpretation: Local Cobb angle correction, increased kyphotic angle, and a decrease in axial stress differential with adjacent and subjacent vertebral levels demonstrate a potential for deformity correction from within the disc space. The decrease in axial stress differential demonstrates a capacity for growth modulation and reversal of the Heuter-Volkmann principle. Based on qualitative views of spinal shape following device implantation, the wedged implant proved more efficacious in correcting single thoracic curves than double major curves. Highlights: A wedged disc implant was designed to counteract the Heuter-Volkmann principle. Finite element analysis of patient spines demonstrated implant efficacy. Deformity correction was quantified using Cobb angle and axial stress distribution. Coronal correction was seen in all patients, of up to 90.1%. Kyphotic normalization was seen in all patients, and reduction of axial stress differential indicated the potential for growth modulation.